Precision assessment of heterogeneity of lymphedema phenotype, genotypes and risk prediction. (October 2016) - Fu, Mei R.; Conley, Yvette P.; Axelrod, Deborah; Guth, Amber A.; Yu, Gary; Fletcher, Jason; Zagzag, David
Abstract: Lymphedema following breast cancer surgery is considered to be mainly due to the mechanical injury from surgery. Recent research identified that inflammation-infection and obesity may be the important predictors for lymphedema. The purpose of this exploratory research was to prospectively examine phenotype of arm lymphedema defined by limb volume and lymphedema symptoms in relation to inflammatory genes in women treated for breast cancer. A prospective, descriptive and repeated-measure design using candidate gene association method was used to enroll 140 women at pre-surgery and followed at 4–8 weeks and 12 months post-surgery. Arm lymphedema was determined by a perometer measurement of ≥5% limb volume increase from baseline of pre-surgery. Lymphedema symptom phenotype was evaluated using a reliable and valid instrument. Saliva samples were collected for DNA extraction. Genes known for inflammation were evaluated, including lymphatic specific growth factors (VEGF-C & VEGF-D), cytokines (IL1- a, IL-4, IL6, IL8, IL10, & IL13), and tumor necrosis factor- a (TNF- a ). No significant associations were found between arm lymphedema phenotype and any inflammatory genetic variations. IL1- a rs17561 was marginally associated with symptom count phenotype of ≥8 symptoms. IL-4 rs2070874 was significantly associated with phenotype of impaired limb mobility and fluid accumulation. Phenotype of fluid accumulation was significantly associated with IL6 rs1800795, IL4 rs2243250 and IL4 rs2070874. Phenotype of discomfort was significantly associated with VEGF-C rs3775203 and IL13 rs1800925. Precision assessment of heterogeneity of lymphedema phenotype and understanding the biological mechanism of each phenotype through the exploration of inherited genetic susceptibility is essential for finding a cure. Further exploration of investigative intervention in the context of genotype and gene expressions would advance our understanding of heterogeneity of lymphedema phenotype. Highlights: Genetic variations may be one of the important factors that influence breast cancer survivors' responses to the inflammatory processes and vulnerability to lymphedema. IL1- a rs17561 was marginally associated with symptom count phenotype of ≥8 symptoms. IL-4 rs2070874 was significantly associated with phenotype of impaired limb mobility and fluid accumulation. Phenotype of fluid accumulation was significantly associated with IL6 rs1800795, IL4 rs2243250 and IL4 rs2070874. Phenotype of discomfort was significantly associated with VEGF-C rs3775203 and IL13 rs1800925.